(untitled) (Proceedings of Southern Federal University. Philology, 2012)
Radchenko I.I. Keywords: negative constructions, mass media texts, intensification means, the category of negation. The article is devoted to the study of the problems connected with the semantics of negative constructions and means of their expressions in mass media texts. The author pays attention to the usage of intensification means and figures based on the category of negation.